The Influence of the Discovery Learning Outcomes in KPK Material for Class IV Students at SD Negeri 5 Banda Aceh - Analia, Syifa; Fauzi, Fauzi; Ahadin, Ahadin; Rauzah, Rauzah (Universitas Syiah Kuala, 2024)
The learning process that focuses on the teacher is actually learning that is not effective, this causing student learning outcomes to drop and do not reach the KKM (Minimum Learning Criteria).The research question in this study is whether there is a significant effect on the use of the Discovery Learning (DL) model on learning outcomes (values) in class IV KPK material at SD Negeri 5Banda Aceh?. The purpose of this study was to find out how significant the influence of the use of the Discovery Learning model was on student learning outcomes in class IV KPK material at SD Negeri 5 Banda Aceh.By using a quantitative approach and equipped with a quasi-experimental design with the type of control group (Pre-Test and Post-Test) Nonequivalent (Nonequivalent pretest and post test Design). The research location is SD Negeri 5 Banda Aceh which is located at Jalan Sultan Alaidin Johansyah, Seutui, Baiturrahman District, Banda Aceh City.The sampling technique used is saturated sampling technique with a sample of all students in grades IV A and IV B with a total of55 students. The test is the main instrument in the form of pretest and posttest. Analysis of the research data used IBM SPSS STATISTIC Version 25 for Windows and the hypothesis was tested with the Paired Samples Test t-test. The results of testing the hypothesis with the Paired Samples Test t-test statistic obtained a significance value (2 tailed) of: 0.000 0.05. Then the conclusion of the results in making a decision is that Ha is accepted and H0 is rejected. Thus it can be concluded that there is a significant influence on the use of the Discovery Learning model on student learning outcomes on KPK material at SD Negeri 5 Banda Aceh.